Remodelling of adult cardiac tissue subjected to physiological and pathological mechanical load in vitro. Issue 3 (16th March 2021) - Pitoulis, Fotios G; Nunez-Toldra, Raquel; Xiao, Ke; Kit-Anan, Worrapong; Mitzka, Saskia; Jabbour, Richard J; Harding, Sian E; Perbellini, Filippo; Thum, Thomas; de Tombe, Pieter P; Terracciano, Cesare M
Abstract: Aims: Cardiac remodelling is the process by which the heart adapts to its environment. Mechanical load is a major driver of remodelling. Cardiac tissue culture has been frequently employed for in vitro studies of load-induced remodelling; however, current in vitro protocols (e.g. cyclic stretch, isometric load, and auxotonic load) are oversimplified and do not accurately capture the dynamic sequence of mechanical conformational changes experienced by the heart in vivo . This limits translational scope and relevance of findings. Methods and results: We developed a novel methodology to study chronic load in vitro . We first developed a bioreactor that can recreate the electromechanical events of in vivo pressure–volume loops as in vitro force–length loops. We then used the bioreactor to culture rat living myocardial slices (LMS) for 3 days. The bioreactor operated based on a 3-Element Windkessel circulatory model enabling tissue mechanical loading based on physiologically relevant parameters of afterload and preload. LMS were continuously stretched/relaxed during culture simulating conditions of physiological load (normal preload and afterload), pressure-overload (normal preload and high afterload), or volume-overload (high preload & normal afterload). At the end of culture, functional, structural, and molecular assays were performed to determine load-induced remodelling. Both pressure- and volume-overloaded LMS showed significantly decreased contractility that was more pronounced in the latter compared with physiological load ( P < 0.0001). Overloaded groups also showed cardiomyocyte hypertrophy; RNAseq identified shared and unique genes expressed in each overload group. The PI3K-Akt pathway was dysregulated in volume-overload while inflammatory pathways were mostly associated with remodelling in pressure-overloaded LMS. Conclusion: We have developed a proof-of-concept platform and methodology to recreate remodelling under pathophysiological load in vitro . We show that LMS cultured in our bioreactor remodel as a function of the type of mechanical load applied to them. Graphical Abstract: